Post-disaster accessibility of basic social and health services for the Subanens in Zamboanga del Norte - Bureros, Narcisa S. (The Threshold: the Official Research Journal of Jose Rizal Memorial State University, Zamboanga del Norte, 2015)
Successful community recovery is the level of health and social vulnerability that exists and the extent to which health and social services are effectively provided. Post-disaster often uncovers health and social inequalities such as differential distribution of resources that often affect racial/ethnic minorities especially those who are situated in remote areas. This study was conducted to look into the post-disaster accessibility of basic health and social services among the Subanen minority in the province of Zamboanga del Norte. It involved 397 Subanen-respondents from the three municipalities of the province, namely: Siayan with 167 respondents, Sindangan with 185, and 45 respondents from Godod. Results showed that the basic health services were least accessed by the respondents. This necessitates the creation of health and social coalition that would foster collaboration among a variety of professionals and allow the province to address specific issues concerning health and social needs as they arise in the Subanen community. This could lead further to public outreach, creation of education programs, and establish long-term monitoring procedures.